2021
DOI: 10.1098/rsbl.2021.0469
|View full text |Cite
|
Sign up to set email alerts
|

Maternal responses to pup calls in a high-cost lactation species

Abstract: Bonding between mothers and their young is fundamental to mammalian reproductive behaviour and individual fitness. In social systems where the risk of confusing filial and non-filial offspring is high, mothers should demonstrate early, strong and consistent responses to their kin throughout the period of offspring dependence, irrespective of maternal traits. We tested this hypothesis through playback experiments in the northern elephant seal Mirounga angustirostris , a phocid species th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In a colonial phocids, the Northern elephant seal, colonies are very large and mothers and pups can be frequently separated due to conspecifics' movements. Northern elephant seal females were also reported to recognize their pup's call within the first 24 hours of life (Linossier et al 2021). Considering that the mothers first foraging trip at sea occurs on average 6 days after parturition, it is more likely that such vocal recognition will be established within the first days of pup's life in CFS.…”
Section: Discussionmentioning
confidence: 99%
“…In a colonial phocids, the Northern elephant seal, colonies are very large and mothers and pups can be frequently separated due to conspecifics' movements. Northern elephant seal females were also reported to recognize their pup's call within the first 24 hours of life (Linossier et al 2021). Considering that the mothers first foraging trip at sea occurs on average 6 days after parturition, it is more likely that such vocal recognition will be established within the first days of pup's life in CFS.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that female Cape fur seals were able to recognize their pup's voice within 2 h after parturition. In other mammal species, the vocal recognition of an offspring by its mother is established later: 24 h in sheep [12], 48 h in mink [11] and goat [13], 24–48 h in the northern elephant seal [18] and 48 h Australian sea lion [16]. Even in humans, only 40% of women succeed in recognizing their own baby's cries after 24 h [2].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally testing the development of the vocal recognition in mother-young pairs of wild mammals within the first hours after birth is challenging for reasons of access to the animals, tracking of births and the ability to conduct experiments. Only a few studies have been carried out so far, involving five domestic [11][12][13][14][15] and five wild species [3,[16][17][18][19] ( pinniped species only). In most cases, individuals were tested from a few days after birth (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Mother-offspring recognition at a distance mostly relies on visual and acoustic cues to infer the position of the young/parent, while recognition at close quarters is mostly sustained by olfaction (Ferreira et al ., 2000; Torriani, Vannoni & McElligott, 2006). In larger groups where risks of confusion are enhanced, accurate parent-offspring recognition prevents misdirected maternal care; particularly when the neonate depends entirely on its mother for food and/or when lactation requires a lot of energy (Sèbe et al ., 2010; Linossier et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%